ILF2 Contributes to Hyperproliferation of Keratinocytes and Skin Inflammation in a KLHDC7B-DT-Dependent Manner in Psoriasis - Yin, Xiran; Yang, Zhenxian; Zhu, Mingsheng; Chen, Cheng; Huang, Shan; Li, Xueqing; Zhong, Hua; Wen, He; Sun, Qing; Yu, Xiaojing; Yan, Jianjun (Frontiers in Genetics, 2022)
Background: The extensive involvement of interleukin enhancer binding factor 2 (ILF2) in RNA stability and inflammation response is well documented. Aberrant long noncoding RNA (lncRNA) expression contributes to the pathogenesis of psoriasis. However, little is known about the role of ILF2 in psoriasis. Objective: To investigate the role of ILF2 and KLHDC7B-DT in psoriasis. Methods: LncRNAs expression in psoriatic tissues was measured by lncRNA microarray and qRT-PCR. Normal human epidermal keratinocytes (NHEKs), HaCaT cells, and Ker-CT cells stimulated by M5 (IL-17A, IL-22, IL-1 α, oncostatin M, and TNF-α) were used to establish a psoriasis model in vitro. Fluorescence in situ hybridization was used to detect the distribution of KLHDC7B-DT and ILF2 in the keratinocytes. The proliferative effects of KLHDC7B-DT and ILF2 on keratinocytes were demonstrated by EdU assay and flow cytometry. ELISA assay was used to detect the secretion levels of cytokines. RNA pull-down and RNA immunoprecipitation (RIP) were used to detect KLHDC7B-DT directly binds with ILF2. Western blotting was used to detect the proteins related to STAT3/JNK signaling pathways. Results: ILF2 and KLHDC7B-DT were significantly overexpressed in psoriatic tissues and M5-induced keratinocytes. KLHDC7B-DT promoted the proliferation of keratinocytes and induced the secretion of IL-6 and IL-8. KLHDC7B-DT could directly bind to ILF2 and activate STAT3 and JNK signalling pathways. The expression of KLHDC7B-DT was regulated by ILF2. M5-induced proliferation and inflammatory cytokines secretion in keratinocytes was inhibited after ILF2 knockdown. Furthermore, we found that ILF2 promoted the keratinocytes’ proliferation and inflammatory response in a KLHDC7B-DT dependent manner. Conclusions: Our findings indicated that ILF2 and KLHDC7B-DT were involved in the hyperproliferation of keratinocytes and skin inflammation in psoriasis. In addition, we verified that ILF2 functioned in a KLHDC7B-DT dependent manner.